Are Japanese Men of Pensionable Age Underemployed or Overemployed? - Emiko Usui; Satoshi Shimizutani; Takashi Oshio (Institute for the Study of Labor (IZA), 2015)
We investigate how Japanese men aged 60-74 adjust their workforce attachment after beginning to receive a public pension. Men who were employees at age 54 gradually move to part-time work or retire after beginning to receive pension benefits; those who continue working are more likely to be underemployed. Men self-employed at age 54, however, neither retire nor reduce their working hours even after beginning to receive pension benefits; these men are more likely to be overemployed. In contrast, U.S. men retire or move to part-time when they first claim Social Security; those who continue working as employees after Social Security starts are unlikely to be either over- or underemployed. Therefore, unlike U.S. men, Japanese men are not choosing the optimal pensionable age and labor hours to maximize their intertemporal utility.
Keywords: J26; I10; H55; 330; Health and Retirement Study (HRS); pension benefits; Japanese Study on Aging and Retirement (JSTAR); work hours; hours constraints; Japan